STUDY OF GEN Z ACCEPTANCE ANALYSIS IN USING DIGITAL QUICK RESPONSE INDONESIA STANDARD (QRIS) AS A DIGITAL TRANSACTION TOOL - Anzie, Luthfy Purnanta; Manalu, Gibson; Savitri, Sherly Dwi Ditzi; Putri, Ramadhani Oktaviana; Zusrony, Edwin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to clarify the relationship between perceived usefulness and perceived ease of use on behavioral intention, with the attitude towards using the QRIS application serving as a mediator. This study focuses on examining the adoption of QRIS as a digital transaction tool among Gen Z. This study utilizes a quantitative approach, involving a sample of 150 Gen Z participants from Central Java Province, chosen through purposive sampling and assessed via a questionnaire instrument. The findings suggest that the perceived usefulness and ease of use significantly impact Gen Z's intention to engage with the QRIS application. Further data suggest that the perceived ease of use does not have a significant impact on attitudes regarding the utilization of variables. This study investigates the application of QRIS technology as a digital payment system through the framework of the Technology Acceptance Model (TAM), focusing on individuals from Generation Z aged 18-25 in Central Java. The findings of the study reveal a favorable impact of perceived utility, perceived ease of use, and attitude towards usage on the behavioral intention regarding the QRIS application. The findings reveal a preference among Generation Z for utilizing digital payment transactions through the QRIS application.